Analisis Permintaan Anak pada Wanita Bekerja di Indonesia - Rayhan, Muhamad; Putri, Dewi Zaini (Universitas Negeri Padang, 2023)
This study aims to analyze; (1) To what extent the influence of the wife's age on the demand for children for working women in Indonesia, (2) How far the influence of the husband's age on the demand for children working women in Indonesia, (3) How far is the influence of the wife's education level on the demand for children for working women in Indonesia, ( 4) The extent to which the influence of husband's education level on the demand for children for working women in Indonesia. (5) The extent to which the influence of the type of wife's work on the demand for children for working women in Indonesia. (6) The extent to which the influence of the husband's working status on the demand for children for working women in Indonesia. (7) The extent to which the influence of the sex preference of children on the demand for children of working women in Indonesia. (8) The extent to which the influence of household income on the demand for children of working women in Indonesia. The data used in this study is cross-sectional data collected from the 2022 KOR SUSENAS data. This research method uses logistic regression analysis techniques. Based on the results of the study: the wife's age, husband's age, wife's education level, husband's education level, wife's type of work, husband's working status, child's gender preference, and household income have a positive and significant effect on children's demand for working women in Indonesia. One of the policies that can be done to reduce fertility rates is the importance of increasing education, especially for women, delaying the age of marriage, and in particular planning for the sex of the child.